Comparison of surgical and non-surgical orthodontic treatment approaches on occlusal and cephalometric outcomes in patients with Class II Division I malocclusions - Sheila Daniels; Patrick Brady; Arya Daniels; Stacey Howes; Kyungsup Shin; Satheesh Elangovan; Veerasathpurush Allareddy (SpringerOpen, 2017)
Abstract Background This study aimed to examine end-of-treatment outcomes of severe Class II Division I malocclusion patients treated with surgical or non-surgical approaches. This study tests the hypotheses that occlusal outcomes (ABO-OGS) and cephalometric outcomes differ between these groups. Methods A total of 60 patients were included: 20 of which underwent surgical correction and 40 of which did not. Cast grading of initial and final study models was performed and information was gathered from pre- to post-treatment cephalometric radiographs. The end-of-treatment ABO-OGS and cephalometric outcomes were compared to Mann-Whitney U tests and multivariable linear regression models. Results Following adjustment for multiple confounders (age, gender, complexity of case, and skeletal patterns), the final deband score (ABO-OGS) was similar for both groups (23.8 for surgical group versus 22.5 for non-surgical group). Those treated surgically had a significantly larger reduction in ANB angle, 3.4° reduction versus 1.5° reduction in the non-surgical group (p = 0.002). The surgical group also showed increased maxillary incisor proclination (p = 0.001) compared to the non-surgical group. This might be attributed to retroclination of maxillary incisors during treatment selection in the non-surgical group-namely, extraction of premolars to mask the discrepancy. Conclusions Those treated surgically had a significantly larger reduction in ANB angle and increased maxillary incisor proclination compared to those treated non-surgically with no significant changes in occlusal outcomes.